2017
DOI: 10.1155/2017/6238106
|View full text |Cite|
|
Sign up to set email alerts
|

Prebiotics: A Novel Approach to Treat Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma is one of the fatal malignancies and is considered as the third leading cause of death. Mutations, genetic modifications, dietary aflatoxins, or impairments in the regulation of oncogenic pathways may bring about liver cancer. An effective barrier against hepatotoxins is offered by gut-liver axis as a change in gut permeability and expanded translocation of lipopolysaccharides triggers the activation of Toll-like receptors which stimulate the process of hepatocarcinogenesis. Prebiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 96 publications
0
16
0
1
Order By: Relevance
“…The same role is exerted also by pro-anthocyanidins, found for example in almonds, grapes and chocolate [329]. Phenols contained in curcumin were reported to be able to arrest cell cycle and inhibit proliferation and metastasis [330].…”
Section: Antioxidant Approach For the Treatment Of Hepatocellular Carmentioning
confidence: 94%
“…The same role is exerted also by pro-anthocyanidins, found for example in almonds, grapes and chocolate [329]. Phenols contained in curcumin were reported to be able to arrest cell cycle and inhibit proliferation and metastasis [330].…”
Section: Antioxidant Approach For the Treatment Of Hepatocellular Carmentioning
confidence: 94%
“…Based on the chemical structure of inulin, the two main groups of prebiotics evaluated in humans are fructans and galactans (Cummings & Macfarlane, ; Fatima, Akhtar, & Sheikh, ). However, the MOS, derived from the cell wall of the yeast Saccharomyces cerevisiae has been gaining research interest (Hajati & Rezaei, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although our results indicated that only miR-196a2 was associated with the susceptibility of HCC, and there was not enough evidence to support the association in miR-146, miR-149 or miR-499, the negative results still could not be ignored and should be interpreted cautiously. This is due to the occurrence of HCC is the result of multiple factors, in addition to complex genetic factors, there are hepatitis, aflatoxin exposure, Hepatitis C virus infection and other factors ( 74 – 76 ). Instead the incidence of HCC, gene variation may only cause increased susceptibility in a certain extent ( 77 ).…”
Section: Discussionmentioning
confidence: 99%